Assessment Of Nutritional Status (With Who Reference Standards) And Health Status Among Rural Primary School Children of Anand District, Gujarat - Donald S Christian; Sidhyartha Mukherjee1 (Medsci Publications, 2016)
Background: Health and Nutritional status school age children of 5-19 years of age are not focused as much as under 5 in India. School age is the foundation of active and productive life for an individual. Methodology: A cross sectional study was done among the enrolled school children (STD 1-7) of a government rural primary school of a village of Anand district, Gujarat. Trained teachers of the school were engaged in measuring height and weights in a standardized way. Measures like BMI for age and Height for age were compared with the WHO growth standards (2007). Results: Among a total of 291 school children (161 boys and 130 girls), for many age groups, more than 80% of children of the groups, were falling below median-2SD of the WHO standards, both for BMI for age and height for age. This was seen more among boys than for girls. The overall prevalence of anemia was 29.20%. Conclusion: Majority of rural primary school children, suffer from significant level of inadequate growth, in terms of body mass and stature. Due to variations in social and economic conditions, the health and nutrition status should be focused for school aged children through more stringent efforts.